Synthesis of Some Polysubstituted Nicotinonitriles and Derived Pyrido[2,3-d]pyrimidines as In Vitro Cytotoxic and Antimicrobial Candidates - Hassan M. Faidallah; Sherif A. F. Rostom; Khalid A. Khan (Journal of Chemistry)
The synthesis of polysubstituted pyridines, in addition to some derived pyrido[2,3-d]pyrimidine ring systems supported with chemotherapeutically active functionalities, is described. They were evaluated for their in vitro cytotoxic effects against three different human tumor cell lines (human colon carcinoma HT29, hepatocellular carcinoma Hep-G2, and Caucasian breast adenocarcinoma MCF7). Nine compounds displayed variable cytotoxic potential, among which alkylthio analogs 33, 34, and 37 emerged as the most active members, being almost twice as active as doxorubicin against the colon carcinoma HT29 cell line. In addition, the same three analogs showed a clear differential cytotoxic profile as they exhibited a marginal inhibitory effect on the growth of the normal nontransformed human foreskin fibroblast Hs27 cell line. Meanwhile, nineteen compounds were able to exhibit significant antibacterial activity against both Gram-positive and Gram-negative bacteria, together with moderate antifungal activities. The pyrido[2,3-d]pyrimidine-2(1H)-thione 30 together with its alkylthio derivatives 33 and 34 stemmed as the most active antimicrobial members being equipotent to ampicillin against S. aureus, E. coli, and P. aeruginosa, together with a noticeable antifungal activity against C. albicans. Compounds 33 and 34 could be considered as a promising template for possible dual antimicrobial-anticancer candidates.